Prognostic factors and overall survival of breast cancer in the city of Goiania, Brazil: a population-based study - Ruffo de Freitas Júnior; Rodrigo Disconzi Nunes; Edesio Martins; Maria Paula Curado; Nilceana Maya Aires Freitas; Leonardo Ribeiro Soares; José Carlos Oliveira (Revista do Colégio Brasileiro de Cirurgiões)
ABSTRACT Objective: to analyze the overall survival and prognostic factors of women with breast cancer in the city of Goiânia. Methods: this is a retrospective, cross-sectional, observational study that included women with malignant neoplasms of the breast identified by the Goiânia Population-based Cancer Registry. The variables studied were age at diagnosis, tumor size, staging, axillary lymph node involvement, tumor grade, disease extent, hormone receptors, and c-erb-B2 oncoprotein. We performed overall survival analyzes of five and ten years. Results: we included 2,273 patients in the study, with an overall survival of 72.1% in five years and 57.8% in ten years. In the multivariate analysis adjusted for tumor size, the factors that influenced the prognosis were axillary lymph nodes, histological grade, progesterone receptor, c erb B2, T staging and disease extension. Conclusion: overall survival in ten years is below that observed in other countries, and possibly reflects what happens with the majority of the Brazilian population. The prognostic factors found in this population follow the same international patterns.